Successful Anesthesia Management in a Patient With Type A Aortic Dissection Complicated by Renal Failure and Suspected Coronavirus Disease. (March 2021) - Zheng, Hongbo; Deng, Qingzhu; Chi, Xiaohui; Chen, Mingbing; Xu, Li; Peng, Yong G.; Wan, Li; Fan, Longchang
Stanford type A acute aortic dissection (AAD) is a life-threatening illness that presents with chest pain and hemodynamic instability. AAD prompt and accurate evaluation and management are critical for survival as it is a cardiac surgical emergency. The initial treatment of AAD mandates strict blood pressure stabilization with intravenous antihypertensive medications. The progressive nature of the disease will increase the mortality as time elapses between diagnosis and surgical intervention. In addition, the patient's blood pressure control is challenged in the presence of renal failure requiring hemodialysis. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 or named 2019-nCoV) pneumonia was a newly underrecognized illness (COVID-19 [coronavirus disease 2019]). COVID-19 can cause severe acute respiratory distress syndrome, acute kidney injury, heart injury, and liver dysfunction, which would aggravate the progress of aortic dissection. In this article, we report the successful anesthesia management in a pneumonia patient with AAD complicated with renal failure during the COVID-19 epidemic period, who underwent emergency surgery and deep hypothermic circulatory arrest repair.